2022
DOI: 10.3389/fchem.2022.956547
|View full text |Cite
|
Sign up to set email alerts
|

Research on the non-point source pollution of microplastics

Abstract: Microplastics are characterized with universality, persistence and toxicity to aquatic organisms, the pollution of microplastics has attracted worldwide attention. At present, studies on microplastic pollution were mainly focused on the composition, abundance and species of microplastics in water bodies and sediments, and few studies were focused on the source and influence characteristics of microplastics in surface water bodies. Starting from the sources of microplastic pollution in surface water of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that the accumulation of film residues can have a significant negative impact on soil quality and crop growth [59][60][61]. Microplastics are now considered to be an important environmental pollutant, almost ubiquitous in the atmosphere, water, soil and other environmental media [62,63]. Specifically, the morphology of microplastic fibers plays a critical role in their capability for long-range atmospheric transport, suggesting that they can traverse vast geographical expanses and exert impacts on the environment [64].…”
Section: Pollution From Agricultural Plastic Filmmentioning
confidence: 99%
“…Studies have shown that the accumulation of film residues can have a significant negative impact on soil quality and crop growth [59][60][61]. Microplastics are now considered to be an important environmental pollutant, almost ubiquitous in the atmosphere, water, soil and other environmental media [62,63]. Specifically, the morphology of microplastic fibers plays a critical role in their capability for long-range atmospheric transport, suggesting that they can traverse vast geographical expanses and exert impacts on the environment [64].…”
Section: Pollution From Agricultural Plastic Filmmentioning
confidence: 99%
“…The soil is seen as a significant reservoir of MP pollution, both absorbing and releasing it [ 39 ]. MPs in polluted soil environments primarily come from agricultural film residues, agricultural irrigation wastewater, organic fertilizers, sludge from wastewater treatment plants, seepage from plastic landfills, waste from plastic products, atmospheric sedimentation, random dumping, improper garbage disposal, and tire wear during car operations [ 40 , 41 , 42 ]. Figure 2 shows the main sources of MPs.…”
Section: Mp Contamination In Soilmentioning
confidence: 99%